Developing English Learning Materials Based On The Emancipated Curriculum For 11th Grade Students Of Senior High School - Ni Putu Wahyu Permatasari; Putu Kerti Nitiasih; Ni Wayan Surya Mahayanti (Journal on Education, 2024)
This research discusses the development of curriculum-based learning materials for class XI SMA second semester. The purpose of this study was to analyze the development of learning materials by using the questionnaire method to student representatives in two schools, (School A) and (School B) questionnaires were distributed through google form obtained the results that school A grade 11 as the research subject was dominated by auditory learning therefore, school A grade 11 students are more dominant auditory learning style. Meanwhile, the value of school B is at the bottom. Based on the results of the questionnaire given by the researcher to school B, the quality of learning materials determines the success of the educational process. Good materials must be organized systematically, relevant to the curriculum and tailored to the level of ability and needs of students.